Starlight : Warriors: The New Prophecy #4 - Hunter, Erin (New York, NY : HarperCollins Children's Books, 2006)
The warrior cat Clans arrive at their new home and set about exploring and fighting over the unfamiliar territory.
Cats/ Fiction/ Fantasy/ Warriors.
Keywords: Cats -- Fiction; Fantasy